Biofeedback to Improve Heart Rate Variability in Patient with Coronary Artery Disease - Fidya Anisa Firdaus; Susi Susilawati (INDOGENIUS, 2026)
Background & Objective: Abstract Coronary artery disease (CAD) is a leading cause of morbidity and mortality worldwide. Patients with CAD often experience decreased heart rate variability (HRV), reflecting an imbalance in the autonomic nervous system and associated with an increased risk of cardiovascular disease. Biofeedback is a non-pharmacological intervention that helps individuals control the body's physiological responses, such as heart rate and breathing, through real-time visual or auditory feedback. The purpose of this article is to examine the role of biofeedback in improving HRV in patients with CAD. Method: The writing method is based on the application of biofeedback as a complementary intervention in patients with CAD, with HRV monitoring before and after the intervention. Biofeedback is performed through controlled breathing exercises and focused relaxation at a specific duration and frequency. Result: The results of the application showed an increase in HRV values ​​after biofeedback, indicating improved autonomic nervous system regulatory function and a reduced stress response. Conclussion: Biofeedback has the potential to be an effective and safe non-pharmacological intervention to improve HRV in patients with CAD and can be recommended as a complementary therapy in nursing practice and cardiac rehabilitation.